A Problem-Posing-Based Critical Literacy Pedagogy Model for Developing Critical Reading Skills among Pre-Service Indonesian Language Educators - Intan Ramdhani; Sumiyani Sumiyani (MASI Mandiri Edukasi, 2026)
Despite the demand for 21st-century skills, literacy is rarely addressed as a transformative power to challenge social structures, and many pre-service teachers still lack sufficient critical reading competence. This study aims to analyze the core conceptual framework of Critical Literacy Pedagogy (CLP) and validate the effectiveness of the problem-posing model in developing the critical reading skills of pre-service Indonesian language educators. The study utilizes a concept analysis and an integrative review design, synthesizing Paulo Freire’s philosophical foundations with empirical validation. The empirical data, adapted from relevant quasi-experimental studies involving 56 pre-service teachers, indicate that the problem-posing model has a highly significant effect (p < 0.005) on all six sub-skills of critical reading. The most substantial improvements were observed in Explanation (F=96.898) and Analysis (F=65.202), signifying a successful pedagogical shift from passive